Schaum's outline of theory and problems of business mathematics - Lerner, Joel J. (Schaum's outline series., 1985)
This title includes 900 solved problems and reviews basic mathematics to calculating insurance terms and explaining the ins and outs of stocks and bonds. It covers all the fundamentals of a business mathematics course and is intended for graduate or professional exams.